Relations between OCBs, organizational justice, work motivation and self-efficacy - Lior Oren; Aharon Tziner; Yulia Nahshon; Gil Sharoni (Amfiteatru Economic Journal, 2013)
The importance of organizational citizenship behaviors (OCBs) in organizations is well documented, and studies that originate from the interactionist perspective and combine personal and situational factors in predicting OCBs are needed. Toward this end, and based on a recent theoretical model, the current study attempted to predict OCB by organizational justice, work motivation, and self-efficacy. A research questionnaire measuring the three predictors was administered to 151 employees, and a measure of their OCB was provided by their supervisors. Whereas OCBs were found to be positively correlated with the three predictors, a hierarchical regression analysis revealed that only organizational justice and work motivation were significant predictors of OCBs. The study emphasizes the importance of using an interactionist perspective integrating endogenous and exogenous forces in studying the antecedents of OCBs. OCBs may be closely related to task performance and may be predicted by motivation related variables. Organizations may facilitate OCBs by improving organizational justice and raising work motivation among employees.
Keywords: D23; M12; 330; organizational citizenship behavior (OCBs); organizational justice; work motivation; self-efficacy